2021
DOI: 10.1186/s12879-021-05883-5
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa device associated – healthcare associated infections and its multidrug resistance at intensive care unit of University Hospital: polish, 8.5-year, prospective, single-centre study

Abstract: Background Pseudomonas aeruginosa has recently shown to be one of the most important strains of bacteria and alert pathogens in Europe among Intensive Care Unit patients that provide serious therapeutic problems because of its multidrug resistance. Methods The purpose of this microbiological study was data analysis of device associated- healthcare associated infections (DA-HAIs) in an ICU in terms of the incidents of P.aeruginosa strain infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen that can cause a variety of infections such as the bloodstream infection, urinary tract infection, burn wound infection and surgical site infection in human bodies ( Litwin et al., 2021 ). Prevention and treatment of its infections are frequently hindered owing to its remarkable capacity of resisting antibiotics, and recurrence of its infections is the leading cause of morbidity and mortality in immunocompromised patients ( Moradali et al., 2017 ; Pang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen that can cause a variety of infections such as the bloodstream infection, urinary tract infection, burn wound infection and surgical site infection in human bodies ( Litwin et al., 2021 ). Prevention and treatment of its infections are frequently hindered owing to its remarkable capacity of resisting antibiotics, and recurrence of its infections is the leading cause of morbidity and mortality in immunocompromised patients ( Moradali et al., 2017 ; Pang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In hospitalized patients, P. aeruginosa is usually associated with acute infections, representing one of the most common causes of hospital-acquired pneumonia (HAP) and the most isolated pathogen in ventilator-associated pneumonia (VAP) (10)(11)(12). Additionally, P. aeruginosa can persist in the lungs of individuals suffering from chronic respiratory diseases, such as cystic fibrosis (CF) or chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa (PA) is a common acquired pathogen, especially important infecting bacteria in diseases such as bronchiectasis, chronic bronchitis, and cystic pulmonary fibrosis. A prospective result suggested a nearly 3-fold increase in the prevalence of PA infection in European intensive care unit patients over an 8.5-year observation period [ 2 ]. Another study showed that the nosocomial infection rate of PA in respiratory intensive care units of teaching hospitals in Northwest China was as high as 10.7% from 2013 to 2015 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%